Serological prevalence of leptospiral infection in wild rats at the National Service Training Centres in Kelantan and Terengganu - Mohamed Hassan, S. N.; Bahaman, Abdul Rani; Mutalib, Abdul Rahim; Bejo, Siti Khairani (Malaysian Society of Parasitology and Tropical Medicine, 2010)
One hundred and sixty eight rats were trapped from the National Service Training Centres (NSTC) in Kelantan and Terengganu from October 2008 to May 2009. Microscopic agglutination test (MAT) was performed to detect the presence of agglutinating antibodies to Leptospira among the rats caught. All the MAT positive rats were identified as Rattus tiomanicus. In Kelantan, 17.3% (14/81) of the rats had leptospiral antibodies to serovars Icterohaemorrhagiae (12.3%), Canicola (2.5%), Ballum (1.2%), and Pyrogenes (1.2%). In Terengganu, 18.4% (16/87) of the rats had antibodies to serovars Icterohaemorrhagiae (15%), Canicola (1.1%), Pyrogenes (1.1%) and Hebdomadis (1.1%). This study indicated that Leptospira serovars were prevalent in the rat population in the study areas and could be a source of infection to humans. Therefore, control of the rat population in all NSTC is critical to prevent outbreaks of leptospirosis amongst the NSTC trainees.